MEMAKSIMALKAN POTENSI GENERASI ALPHA UNTUK MENYONGSONG INDONESIA EMAS 2045 - Andianti, Yohana Putri; Dwikurnaningsih , Yari; Loekmono , J. T. Lobby (Realita : Jurnal Bimbingan dan Konseling, 2025)
The purpose of this research is to examine the potential of Generation Alpha, as well as the education and guidance needed to prepare them for Indonesia Gold 2045. This study uses a descriptive qualitative approach, employing initial observations, limited interviews with guidance teachers and counselors, and parents of Generation Alpha. The research results show that Generation Alpha has advantages in creativity, independent learning ability, and technology mastery. However, as a result of the dominance of virtual interactions, they also face significant problems, such as technology addiction, difficulty managing emotions, and a lack of social concern. This research emphasizes that integrated career guidance services must be provided from the beginning. It is also important to enhance 21st-century skills such as critical thinking, collaboration, communication, and character development. To realize Indonesia Gold 2045, schools, families, and the surrounding environment must work together to maximize the potential of Generation Alpha. This will become a productive and competitive agent of change worldwide.